Rally around the EU flag! Supra-nationalism in the light of Islamist terrorism - Anna Nowak (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2019)
Terror attacks are known to increase support for the attacked nation state and strengthen ingroup affiliations among citizens. Even though there is evidence that a terror attack can affect people all over the world, up to now no study has considered whether these nation-specific effects work on a supra-national level. This study investigates these effects by analyzing the impact of two severe Islamist terror attacks, the Paris attack from 2015 and the Manchester bombing from 2017, on citizens' attachment to the European Union (EU). We use data from the Eurobarometer surveys that were conducted around the time of these attacks. Applying an entropy- balancing approach before running ordered logistic regressions, we make use of the quasi-random variation in survey interviews to analyze the treatment effects of the two attacks. The results indicate that the so-called rally effects work for supra-national communities and that they increase EU citizens' attachment to and the identification with the EU. Thus, the study has relevant implications for research about terror attacks, as it provides new insights about the scope of rally effects and their mode of operation.
Keywords: D74; F51; F53; H12; 330; terrorism; rally effect; EU attachment; identity